(untitled) (Bangladesh Journal of Urology, 2025)
Background: Traditional end-to-side (ETS) anastomosis is a common technique for radiocephalic arteriovenous fistula (RCAVF) creation. However, Side-to-side anastomosis with distal cephalic vein ligation produces a functional ETS anastomosis which showed better outcomes. This study aimed to determine the best anastomotic technique between functional and traditional ETS anastomosis. Methods: This single-blind randomized controlled trial was performed in the Department of Urology, Chittagong Medical College Hospital from May 2022 to May 2023. 100 adult patients with ESKD requiring new RCAVF were the study population. Patients were allocated randomly into functional and traditional ETS groups. Pre and postoperative duplex ultrasonograms were performed by the same radiologist and all anastomoses were performed by a single surgeon to avoid inter-personal variation. Patients were followed up for 12 weeks postoperatively. Results: Both study groups were comparable in terms of their demographic and clinical characteristics. The 12-week patency rate was higher (p=0.362) in the functional ETS 48 (98.0%) than the traditional 46 (92.0%). Fistula became mature in 46(93.9%) of cases in the functional ETS group and 38 (76.0%) in traditional ETS and the difference is statistically significant (p=0.013). In the functional ETS group, 1(2%) of patients developed thrombosis, 1(2%) oedema and 1(2%) pseudoaneurysm. In traditional ETS, 3(6%) of patients developed thrombosis, 1(2%) oedema and 2(4%) pseudoaneurysm. Conclusion: Functional ETS anastomosis has a better short-term outcome than traditional ETS. So, it can be a recommended anastomosis procedure for RCAVF surgery. Bangladesh J. Urol. 2025; 28(1): 33-38